Temperature studies of optical parameters in (Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin films - Studenyak, I.P.; Kutsyk, M.M.; Rati, Y.Y.; Izai, V.Yu.; Kökényesi, S.; Daróci, L.; Bohdan, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
(Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin films were deposited onto a silica substrate by using rapid thermal evaporation. The surfaces of the films were covered with Ag-rich crystalline micrometer-sized cones. The optical transmission spectra of thin films were studied within the temperature range 77…300 K. The absorption spectra in the region of its exponential behaviour were analysed, the dispersion dependences of refractive index as well as the temperature dependences of energy position of absorption edge and Urbach energy were investigated.